Analisis Karakteristik Bahasa Jurnalistik Pada Media Online Sindonews.com Edisi Februari 2023 Dan Pemanfaatannya Sebagai Bahan Ajar Teks Berita Di SMP Kelas VIII - Saputri, Finna Aulia; Mujtaba, Sahlan; Adham, M.Januar Ibnu (Peneliti.net, 2023)
This study aims (1) to describe the use of journalistic language characteristics on news media portals online Sindonews.com in the Metro Sindo channel, February 2023 edition, (2) to describe the results of the research as teaching materials for news texts in the form of modules for grade VIII junior high schools (SMP). The theory used in this study is the Sumadiria theory (2016). The research and method used in this research is descriptive qualitative research. The data collection technique used in the research is a note-taking technique. Based on the results of media research online sindonews.com during its February 2023 issue has used journalistic language characteristics that are easy to understand. However, there were still 8 that did not fit the simple characteristics, 5 did not fit the short characteristics, 4 did not fit the clear characteristics, 11 did not fit the populist characteristics, 8 did not fit the grammatical characteristics, 9 did not fit the avoidance characteristics, 10 did not fit the characteristics of avoiding foreign words and terms, 11 did not fit the characteristics of diction choice, and 4 did not fit the characteristics of avoiding words or technical terms. From the results of the analysis obtained, its use in further education can be used as teaching materials in the form of modules that are applied in learning news texts in accordance with Basic Competency (KD) 3.2 Examining the Structure and Language Rules of News Texts.